Citizen Science : Public Participation in Environmental Research - Fitzpatrick, John W.; Louv, Richard; Bonney, Rick, 1954-; Dickinson, Janis L., 1955- (Book collections on Project MUSE., 2012)
In Citizen Science, experts from a variety of disciplines share their experiences of creating and implementing successful citizen science projects, primarily those that use massive data sets gathered by citizen scientists to better understand the impact of environmental change. This first and foundational book for this developing field of inquiry addresses basic aspects of how to conduct citizen science projects, including goal-setting, program design, and evaluation, as well as the nuances of creating a robust digital infrastructure and recruiting a large participant base through communications and marketing. An overview of the types of research approaches and techniques demonstrates how to make use of large data sets arising from citizen science projects. A final section focuses on citizen science's impacts and its broad connections to understanding the human dimensions and educational aspects of participation. Intended as a resource for a broad audience of experts and practitioners in natural sciences, information science, and social sciences, this book can be used to better understand how to improve existing programs, develop new ones, and make better use of the data resources that have accumulated from citizen science efforts. Its focus on harnessing the impact of "crowdsourcing" for scientific and educational endeavors is applicable to a wide range of fields, especially those that touch on the importance of massive collaboration aimed at understanding and conserving what we can of the natural world.